THE DYNAMICS OF ACCEPTANCE AND RESISTANCE TO PRODUCTIVE WAQF: A Case Study of Mathali’ul Anwar and Al-Ishlah in Lamongan - Azzam Musoffa; Syah Wardi; Muhammad Jihad Albanna; Rasfiuddin Sabaruddin; Hilda Lutfiani (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2024)
This study aims to compare two productive waqf approaches in two boarding schools in Lamongan, namely Mathali'ul Anwar and Al-Ishlah through the lens of Max Weber's rational theory. The research method in this study uses a qualitative approach with data collection through interviews to understand the practice of productive waqf in both institutions. It was found that the dynamics of resistance to the application of productive waqf in Mathali'ul Anwar were then analyzed with theory of rationalization and the researcher concluded that the incident was in accordance with the concept of instrumental rational (zweckrational). The resistance to productive waqf found in Al-Ishlah can be understood in accordance with value-based rational concept (wertrational). This is concluded from the view of Kiai Khotib in developing productive waqf at Mathali'ul Anwar which is implemented systematically so that there is a change in social conditions in the form of acceptance of the waqf practice. Unlike the case in Al-Ishlah, Kiai Dawam's strong stance on the value of education causes other values to be displaced, including productive waqf based on economic independence. In addition, the results of this study also prove that James Peacock's typology of santri is refuted, that division of santri into reformist and traditionalist santri does not apply in this productive waqf case.